Packet contention resolution in slotted optical packet switch using ant-colony based algorithm - Tan, Shing Chiang; Abbou, F. M.; Ewe, Hong Tat (The Institution of Engineering and Technology, 2007)
An ant-based contention resolution scheme for the slotted optical packet switched networks has been proposed, and the optimal number of fibre delay lines (FDLs) used in the switch under various traffic loads is investigated. The proposed algorithm can makes FDLs and output port assignment: so as to improve the cell-loss rate under various traffic loads. It is found for traffic loads 0.9, 0.6, 0.3, the optimum value for FDL is 64 128 and 128.